(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The aim of this paper is to find the inversion of such integral equations whose kernel involves many well known classical polynomials like those of Hermite, Laguerre, Bessel, Legendre, Jacobi etc. We believe that many polynomials can be obtained by considering suitable parameters involved in Generalized Hermite Polynomial. For the purpose of illustration we took a Bessel polynomial in form of Generalized Hermite Polynomial by choosing suitable parameters involved in it.